2008
DOI: 10.2146/ajhp060352
|View full text |Cite
|
Sign up to set email alerts
|

Gene-expression assays: New tools to individualize treatment of early-stage breast cancer

Abstract: Two gene-expression assays, Oncotype DX and MammaPrint, have been developed to determine the risk of breast cancer recurrence in patients with stage I or II node-negative breast cancer. In the future, these tests may be useful in determining the need for systemic adjuvant therapy in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 11 publications
0
16
0
2
Order By: Relevance
“…The gene profiles used to develop CMTC were derived from a commercially available whole-genome microarray platform that has become more affordable than currently available multigene assays, such as MammaPrint (70GS; Agendia Inc, Irvine, CA, USA) and Oncotype DX (Genomic Health, Redwood City, CA, USA), which report only a limited number of genes [24,45] at a high cost [19,50]. Furthermore, the clinical application of CMTC may be extended to other commercial genome-wide microarray platforms, as we have demonstrated the reproducibility of CMTC classification in the validation cohort derived independently from different DNA microarray platforms.…”
Section: Discussionmentioning
confidence: 99%
“…The gene profiles used to develop CMTC were derived from a commercially available whole-genome microarray platform that has become more affordable than currently available multigene assays, such as MammaPrint (70GS; Agendia Inc, Irvine, CA, USA) and Oncotype DX (Genomic Health, Redwood City, CA, USA), which report only a limited number of genes [24,45] at a high cost [19,50]. Furthermore, the clinical application of CMTC may be extended to other commercial genome-wide microarray platforms, as we have demonstrated the reproducibility of CMTC classification in the validation cohort derived independently from different DNA microarray platforms.…”
Section: Discussionmentioning
confidence: 99%
“…The development in oncogene profiling in the last decade has slowly been established as clinical tools. For example, Oncotype DXÒ on the basis of 21 genes has been shown to predict 10-year distant recurrence in patients with estrogen receptor-positive, axillary lymph node-negative breast cancer [10,11]. The wide spread use of these tools is expected to provide additional prognostic predictors other than the traditional tumor staging and node status to determine the optimal management for each patient.…”
mentioning
confidence: 99%
“…Several novel prognostic indices of breast cancer were reported [2,20,49,56]. Miller et al [49] reported that the expression patterns of 84 elements, which were extracted from 23,343 unique genetic elements of cDNA microarrays from 26 tumors, had the potential to distinguish high and low Nottingham Prognostic Index patient samples.…”
Section: Discussionmentioning
confidence: 99%
“…Dobbe et al reviewed two gene expression assays and concluded that the two gene expression assays, Oncotype DX and MammaPrint, have been developed to determine the risk of breast cancer recurrence in patients with stage I or II node-negative breast cancer. In the future, these tests may be useful in determining the need for systemic adjuvant therapy in such patients [20]. Asaka et al [2] constructed a novel genetic prognostic index among node-positive breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%